Infantile Spasms and Trisomy 21: Unfavorable Outcomes with First-line Vigabatrin Therapy. (21st November 2021) - Datta, Anita N.; Crawford, Jacqueline; Wong, Peter K.H.
ABSTRACT: Introduction: Among children with infantile spasms (ISs), those with trisomy 21 (T21) and those with normal development at onset and no identifiable etiology (previously referred to as "idiopathic") are expected to have relatively favorable outcomes. The study objective is to determine if differences exist in treatment response, relapse, and subsequent epilepsy between these two groups when vigabatrin is used as first-line treatment. Methods: In this retrospective study, patients were classified into the following groups and clinical features were compared: T21 (n = 24) and IS with normal development at onset and no identified etiology (n = 40; control group). Results: There was no significant difference in the age of IS onset, sex distribution, or treatment lag between the groups. The T21 compared to the control group required a higher mean number of anti-seizure therapies (3.6 vs. 1.9, p < 0.001), had more relapses [10 (42%) vs. 4 (10%), p < 0.005)], and had higher risk of subsequent epilepsy [11 (46%) vs. 8 (20%), p < 0.003]. Relapses were often delayed in the T21 group, with a mean of 8 months after IS cessation. Conclusion: Our results differ from most studies using steroids as first-line treatment where the groups were shown to have similar treatment response and T21 patients had a low risk of relapse and subsequent epilepsy. Therefore, our results suggest that vigabatrin as first-line treatment in T21 with IS may be less favorable than steroids.